The Influence of Financial Performance and Macroeconomic Factors on Price to Book Value in Property and Real estate Companies in Indonesia - Abet Alpha Pardede; R.A. Widyanti Diah Lestari; Nolla Puspita Dewi; Sumantri (Jurnal Akuntansi, 2025)
The objective of this research is to assess the contribution of several financial indicators on market valuation of the firm. The company's financial setup is represented as quantified by the proportion of debt to equity, through the Equity Ratio (DER). A company's liquidity is reflected through the Current Ratio (CR), while profitability is indicated as Return on Equity ((ROE). The effects of these financial indicators on firm valuation are analyzed using Price to Book Value (PBV) as an indicator of market valuation. Additionally, this analysis looks into the importance of inflation functioning as an interaction variable that may affect the interactions among those financial metrics. The analysis draws upon data from 52 companies operating spanning the property and real estate market, whose shares were actively traded on the national trading exchange of Indonesia during the 2019–2023 period. The analytical framework employs panel data regression utilizing the Random Effect Model (REM), supported by interaction testing to evaluate moderation effects. The findings reveal that DER exerts a positive and statistically substantial effect on Price to Book Value, particularly for firms categorized as undervalued. In contrast, CR exhibits a negative effect, while ROE does not show a significant correlation with the company’s value. Moreover, inflation serving as a moderating factor in the relationship among financial ratios and the value of undervalued firms.